Pasta Street / Nur Adlina Ahmadani - Ahmadani, Nur Adlina (2021)
Online marketing is a process of utilizing web-based platforms to distribute information about the company’s brand, products, or services that are offered to potential consumers. It is tools and techniques by using the internet in promoting the business as widely. There are few advantages of online marketing rather than traditional marketing such as potential expansion, improved control and customer services, and competitive advantages. This report will focus on how to handle the online business in social media such as Facebook (FB) to attract potential customers in buying our products in Pasta Street. Pasta Street is a food and beverage business where it is providing Italian and Mexican foods where it is a simple and delicious cuisine. It is a favorite dish from all around of world and Malaysia is known for its various food from traditional food to international food such as Western food, Chinese food, and others. The purpose of this assignment is to understand how online business becomes get become well known through online marketing. The strategy in extending the online business to promoting the products locally by using teasers, soft sells, and hard sells. The teaser will give the general ideas of the company brands and products to captivate the recognition of the customers. Then, soft sell will highlight the food products’ advantages and relate to the customers feeling by engaging humor or connecting with warm and pleasant images. While for hard sells, it is used to encourage the customer to buy the product immediately rather than considering their choices and may postponing the purchase. With this approach, it can build a good image and trusty to the customer besides increasing their interest and willingness to try the homemade foods by Pasta Street.